2001
DOI: 10.1180/002646101750377515
|View full text |Cite
|
Sign up to set email alerts
|

A fluid inclusion study of an amethyst deposit in the Cretaceous Kyongsang Basin, South Korea

Abstract: ABSTR ACTThe Eonyang amethyst deposit is thought to be spatially and temporally associated with the biotite granite of the Cretaceous Kyongsang Basin, South Korea. The euhedral quartz crystals in cavities in the aplite which intrudes biotite granite are colour-zoned from white at the base to amethystine at the top. Fluid inclusions from rock-forming quartz in granitic rocks and euhedral quartz crystals in cavities were examined. Three types of primary inclusions were observed and three isochores for inclusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Therefore, the true trapping temperature (T t ) for Type 1 fluids is~390 • C. This modelled crystallisation temperature is within the 370 • C to 420 • C range published by Thomas et al [13] from fluid inclusion studies of Brazilian quartz amethyst geodes. Similar fluid inclusion studies by Yang et al [21] reported temperatures of between 280 • C and 400 • C for amethyst crystallisation in granite miaroles of the Eonyang deposit, South Korea. …”
Section: Pressure-temperature Modelling Of Type 1 Fluid Inclusionssupporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, the true trapping temperature (T t ) for Type 1 fluids is~390 • C. This modelled crystallisation temperature is within the 370 • C to 420 • C range published by Thomas et al [13] from fluid inclusion studies of Brazilian quartz amethyst geodes. Similar fluid inclusion studies by Yang et al [21] reported temperatures of between 280 • C and 400 • C for amethyst crystallisation in granite miaroles of the Eonyang deposit, South Korea. …”
Section: Pressure-temperature Modelling Of Type 1 Fluid Inclusionssupporting
confidence: 79%
“…Gem quality amethyst, e.g., from Brazil and Uruguay come from geodes in basaltic rocks of the Parana Continental Flood Basalt Province [12]. Published crystallisation temperatures of amethyst cover a wide range, e.g., (1) 370 to 420 • C from fluid inclusion studies of Brazilian geodes [13]; (2) <50 • C fluid inclusion data from Brazilian amethyst [14]; (3) stable oxygen isotope data from amethyst and agate hosted in the Prana-Etendka volcanics [14] and in Devonian and Tertiary volcanics of Scotland [15,16] indicate temperatures <150 • C; (4) Granite hosted amethyst veins from Thunder Bay, Canada, are considered to have formed between 40 and 90 • C [17]; (5) amethysts from epithermal polymetallic veins have formation temperatures ranging between 150 and 250 • C based on fluid inclusion studies [18][19][20] and (6) higher fluid-inclusion homogenization temperatures (280-400 • C) were reported from amethyst in granite miaroles of the Eonyang deposit, South Korea [21]. Finally, such high temperatures are also used in laboratory-based hydrothermal amethyst synthesis [18].…”
Section: Introductionmentioning
confidence: 99%
“…Gilg et al (2003) and Commin-Fischer et al (2010) reported maximum trapping temperatures of 100°C and low salinity fluids for amethyst hosted in basalt cavities of Rio Grande do Sul, Brazil. For amethyst related to Cretaceous granite in South Korea, Yang et al (2001) discussed higher formation temperatures, between 280°C and 400°C, and average salinity of 4 wt.% NaCl equivalent. Dumanska-Slowik et al (2017) studied fluid inclusions trapped in amethyst associated with Lower Cambrian siltstone-sandstone, and report homogenization temperatures between 210°C and 330°C and salinity values between 6 and 13 wt.% NaCl equivalent.…”
Section: Introductionmentioning
confidence: 99%
“…Gilg et al (2003) and Commin-Fischer et al (2010) reported maximum trapping temperatures of 100°C and low-salinity fluids for amethyst hosted in basalt cavities at Rio Grande do Sul, Brazil. For amethyst related to Cretaceous granite in South Korea, Yang et al (2001) discussed higher formation temperatures, between 280°C and 400°C, and average salinity of 4 eq. wt.% NaCl.…”
Section: Introductionmentioning
confidence: 99%
“…The Sannae W-Mo deposit is a vein-type scheelite-wolframite-molybdenite-bearing deposit [27,28]. The Eonyang amethyst deposit [29][30][31][32] is associated with an aplitic part in the granite and contains a series of UST sequences consisting of quartz and feldspar, in which quartz crystals have developed a clear zonation along the c-axis (Figure 2). The quartz crystals in the USTs and phenocrysts of the associated aplite contain melt and fluid inclusions.…”
Section: Introductionmentioning
confidence: 99%